Diagnosis of closed injury and neoplasm of the brachial plexus by ultrasonography. Issue 7 (26th March 2014) - Zheng, Minjuan; Zhu, Yongsheng; Zhou, Xiaodong; Chen, Susan; Cong, Rui; Chen, Dingzhang
ABSTRACT Purpose To evaluate the feasibility and accuracy of high‐frequency sonography (US) in diagnosing traumatic brachial plexus (BP) lesions and neoplasms in the adult. Methods Eleven patients with suspected BP closed trauma, 6 patients with BP neoplasm, and 12 healthy volunteers were scanned. The US findings were compared with surgical findings. Results The interscalene space and intervertebral foramina were useful anatomic markers in identifying the BP. In the 24 sites examined in the normal group (12 subjects examined on both sides), the fifth to seventh cervical nerve roots (C5–7, including upper and middle trunk) were seen, whereas the eighth cervical and first thoracic nerve roots (C8, T1, including the lower trunk) were seen in 91.7% (22/24) of the subjects. The BP appeared as three or four discrete rounded hypoechoic nodules between the anterior scalene and middle scalene muscle in transverse views at the C5–7 level, representing the trunks in the sagittal oblique section. In the BP trauma group (n = 11), the normal nerve trunk was interrupted, and lesions were shown as thickening and swelling with indistinct inner structures. In the neoplasm group (n = 6), masses were shown as hypoechoic masses. Conclusions High‐frequency US is valuable in diagnosing BP closed injuries and neoplasms. © 2014 Wiley Periodicals, Inc. J Clin Ultrasound42:417–422, 2014